2009
DOI: 10.1186/2046-0481-62-s4-s59
|View full text |Cite
|
Sign up to set email alerts
|

Changing trends in mastitis

Abstract: The global dairy industry, the predominant pathogens causing mastitis, our understanding of mastitis pathogens and the host response to intramammary infection are changing rapidly. This paper aims to discuss changes in each of these aspects. Globalisation, energy demands, human population growth and climate change all affect the dairy industry. In many western countries, control programs for contagious mastitis have been in place for decades, resulting in a decrease in occurrence of Streptococcus agalactiae an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
67
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(74 citation statements)
references
References 158 publications
(192 reference statements)
2
67
0
5
Order By: Relevance
“…This is mainly due to the difficulties in routine diagnostics, persistence of staphylococcal infections and abundance of S. aureus in the environment. The bacteria can be found on the skin of bovine and non-bovine animals, on the skin of staff, on milking equipment, flies, and throughout the barn or farm area (Zadoks and Fitzpatrick 2009). It is therefore important to determine the source and the nature of the mastitis infection, which may demonstrate a clonal, subclonal or ecological character.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is mainly due to the difficulties in routine diagnostics, persistence of staphylococcal infections and abundance of S. aureus in the environment. The bacteria can be found on the skin of bovine and non-bovine animals, on the skin of staff, on milking equipment, flies, and throughout the barn or farm area (Zadoks and Fitzpatrick 2009). It is therefore important to determine the source and the nature of the mastitis infection, which may demonstrate a clonal, subclonal or ecological character.…”
Section: Discussionmentioning
confidence: 99%
“…Mastitis, inflammation of the mammary gland, is one of the most common infections caused by staphylococci among livestock, and is associated with significant economic losses in farming and the dairy industry. Among the many species of bacteria that cause mastitis in cattle, Staphylococcus aureus is mentioned as one of the most contagious and common etiologic factors of this disease (Zadoks and Fitzpatrick 2009, Le Marechal et al 2011, Peton and Le Loir 2013. Staphylococci are isolated from the mastitic milk of animals suffering from an acute inflammation of the udder, but more frequently from cows that exhibit or do not exhibit any clinical manifestation of the disease (subclinical mastitis).…”
Section: Introductionmentioning
confidence: 99%
“…International studies have identified large variation in the pathogens deemed to be the predominant cause of mastitis depending on geographical location, production system and local mastitis control programmes (Zadoks and Fitzpatrick 2009). There is a dearth of information on the aetiology of mastitis on Irish farms.…”
Section: Introductionmentioning
confidence: 99%
“…Statements about the associations between MAM and risk factors are therefore more comprehensive and less specific than those made for each individual mastitis indicator. The methodology is not adequate to find management strategies effective against particular mammary pathogens but it is suited to studies, like ours, with the objective of identifying factors influencing herd mastitis in a global manner, given that trends in mastitis have changed over the last 50 years and that different mastitis pathogens are predominant in different herds, regions and countries (Zadoks and Fitzpatrick, 2009). …”
Section: Discussionmentioning
confidence: 99%